Glorifying the Protagonists as Heroes: A Critique of Hemingway’s The Old Man and the Sea and Sarubhakta’s The Peak - Dhakal, Sibu (The Outlook: Journal of English Studies, 2025)
This study brings together Ernest Hemingway’s The Old Man and the Sea and Sarubhakta’s Chuli (The Peak) with a significant focus on a comparative analysis of the flaws of the protagonists in both the novels, which basically delve into the epic battle of the protagonists with the environment. Hemingway’s protagonist, Santiago, involves in a struggle with the sea while Sarubhakta’s unnamed protagonist confronts the formidable challenge with the mountain. Both the protagonists struggle for achieving something significant. Santiago’s is a battle to catch the marlin whereas the unnamed mountaineer’s battle in Sarubhakta’s The Peak is to get victory over the Everest. This study scrutinizes the flaws of the protagonists by analyzing their behaviour and motivations. This research is strictly based on textual evidence and analysis, employing the insights of theory of heroism as a theoretical tool. A significant study of literature gives a shape to understanding the character of the protagonists in depth. The research challenges the idealized portrayals of these protagonists, arguing that they have been unnecessarily glorified. Ultimately, the study concludes that these characters fall short of the heroic ideals they are often associated with and may no longer serve as ideal characters for contemporary readers.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />